Tropical tall forests are more sensitive and vulnerable to drought than short forests. (9th December 2021) - Liu, Liyang; Chen, Xiuzhi; Ciais, Philippe; Yuan, Wenping; Maignan, Fabienne; Wu, Jin; Piao, Shilong; Wang, Ying‐Ping; Wigneron, Jean‐Pierre; Fan, Lei; Gentine, Pierre; Yang, Xueqin; et al.
Abstract: Our limited understanding of the impacts of drought on tropical forests significantly impedes our ability in accurately predicting the impacts of climate change on this biome. Here, we investigated the impact of drought on the dynamics of forest canopies with different heights using time‐series records of remotely sensed Ku‐band vegetation optical depth (Ku‐VOD), a proxy of top‐canopy foliar mass and water content, and separated the signal of Ku‐VOD changes into drought‐induced reductions and subsequent non‐drought gains. Both drought‐induced reductions and non‐drought increases in Ku‐VOD varied significantly with canopy height. Taller tropical forests experienced greater relative Ku‐VOD reductions during drought and larger non‐drought increases than shorter forests, but the net effect of drought was more negative in the taller forests. Meta‐analysis of in situ hydraulic traits supports the hypothesis that taller tropical forests are more vulnerable to drought stress due to smaller xylem‐transport safety margins. Additionally, Ku‐VOD of taller forests showed larger reductions due to increased atmospheric dryness, as assessed by vapor pressure deficit, and showed larger gains in response to enhanced water supply than shorter forests. Including the height‐dependent variation of hydraulic transport in ecosystem models will improve the simulated response of tropical forests to drought. Abstract : Taller tropical forests experienced greater relative canopy reductions during drought and larger non‐drought increases than shorter forests, but the net effect of drought was more negative in the taller forests. Meta‐analysis of in situ hydraulic traits supports the hypothesis that taller tropical forests are more vulnerable to drought stress due to smaller xylem‐transport safety margins. The hydraulic failure and carbon starvation hypotheses are two main non‐mutually exclusive theories to explain drought‐induced dynamics of tropical forests because of significant carbon–hydraulic interactions.